Transformasi Digital untuk Mewujudkan Ruang Publik Yang Lebih Cerdas - Haryani, Haryani; Agustiani, Sarifah; Junaidi, Agus; Wahyudin, Wahyudin (Jurnal Abdimas Ekonomi dan Bisnis, 2024)
The purpose of this activity is to provide solutions to problems in RPTRA in the form of RPTRA management information systems and provide information technology training in the form of RPTRA website management. The problem in the management of RPTRA so far is that there has been no integrated data, both data on guest visits, activity agendas, and events carried out by RPTRA and external parties that use the Annur RPTRA land. The main problems related to digital infrastructure at RPTRA Annur are the availability of access to digital information such as the use of devices for digital learning for children, access to information and online registration of activities, communication and coordination between RPTRA managers and the community. The expected result in Community Service at RPTRA Annur is to make a product in the form of an RPTRA website profile that contains an agenda of activities and events, and a guest visit book that uses land at RPTRA. In addition, with this digital transformation activity, RPTRA managers also gain increased knowledge in using the Canva application for the learning process carried out.